(untitled) (Agroindustrial Science, 2025)
The objective of the research was to evaluate the effects on vegetative development of V. pompona cuttings inoculated with Trichoderma strains, carried out within the territory of the native community of Alto Naranjillo. The strain was isolated from a soil sample of secondary forest and reproduced on sterilized rice grain. Doses of 20 and 40 grams per cutting were applied in two experimental designs: a completely randomized design with 4-node cuttings and a block design with 3, 4, 5 and 6-node cuttings. The cuttings were planted in leaf litter under controlled shade conditions. The results showed that cuttings inoculated with 40 grams of native Trichoderma developed more shoots and roots than the controls and the commercial strain Trichoderma harzianum. The highest number of shoots and roots was obtained on cuttings with 5 and 6 nodes, and under a shade level of 57-60%, this being the most favorable environment. It is concluded that the use of native Trichoderma ghanense is effective in promoting the vegetative development of Vanilla pompona, offering a sustainable alternative to the use of agrochemicals.